PERLINDUNGAN HAK CIPTA LAGU TERHADAP LAYANAN AGREGATOR MUSIK - Amanda Febrianthi Soeyatno, (2022)
The purpose of this study was to determine the application of the provisions of protection and law enforcement against users of music aggregators in terms of the legal system in Indonesia. Data were collected from several cases experienced by both bands and local label records. The research method used in this paper is juridical-normative, in which the author tries to provide an overview, identify, and classify the types of protection and legal remedies that apply to the cases used. The results of this paper explain that overall UUHC has provided full protection of copyright, especially in the field of music in the current digital era, but, unfortunately, there is still a legal vacuum against one of the contributors to music distribution in the independent music scene, namely music aggregators. The author also finds that there are several types of active violations caused by several aggregators in providing their services which result in. It is hoped that the results of this study can provide benefits and become an educational tool for readers in organizing.